Pengaruh earning per share, net profit margin, price earning ratio terhadap return saham - Sarah Rafi Wulandari (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
The research aims to provide empirical evidence of the relationship between Earning Per Share (EPS), Net Profit Margin (NPM), and Price Earning Ratio (PER) on stock returns. Data sample companies are listed on IDX in the Property and Real Estate sector for the 2012-2016 period using the purposive sampling method. Based on the analysis using multiple linear regression, the results of the study prove that earnings per share can affect stock returns. Whereas Net Profit Margin and Price Earning Ratio have no significant effect on stock returns. This research can provide practitioners with useful information to evaluate the factors that influence stock returns in the property and real estate sector.